Penentuan Lokasi Potensial Pengembangan Kawasan Permukiman Berbasis GIS di Kota Parepare - Akhim Tikara; Arifuddin Akil; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
The annual increase in population in Parepare City has an impact on increasing the need for residential land, while there is limited land in the city center which causes the need for land to be directed to suburban areas which are in hill and mountainous areas. This study aimed to determine the land suitability for the development of residential areas in the Parepare highlands zone. The primary data was collected through filed observation, questionnaires and interviews, while the secondary data was gained from literature studies, visit to relevant local agencies, map interpretation and digitization. The analysis used descriptive qualitative, scalogram, Analytical Hierarchy Process (AHP), scoring, and spatial analysis. This research was conducted from January to June 2022. The results showed that most of the existing residential areas that are supported by facilities are located in Bacukiki District where land suitability can be divided into three categories, i.e., high, moderate and poor. Based on the analysis, this paper suggested that the area that are highly suitable can be developed as residential area as well as the moderate however the latter must be preconditioned in order to meet minimum qualification, meanwhile the rest of the area that area poorly potential may be preserved as a conservation area instead of residential function.